"Voices from the Shop Floor: Labour Policy Awareness Among SME Employees in Karnataka" with reference to Dharwad District (International Journal of Environmental Sciences, 2025)
In India’s rapidly expanding industrial landscape, Small and Medium Enterprises (SMEs) play a pivotal role in employment generation and economic contribution. However, the awareness and implementation of labour policies within these enterprises often remain inadequate, particularly at the shop-floor level. This study investigates the level of awareness among SME employees in Dharwad District regarding key labour laws, including provisions related to minimum wages, social security, occupational safety, working hours, and grievance redressal mechanisms. The objective is to identify knowledge gaps, assess compliance challenges, and understand employee perceptions of workplace rights and entitlements.A structured questionnaire was administered to a representative sample of shop-floor employees across multiple SME clusters in Dharwad. Quantitative data were statistically analyzed using frequency distribution, cross-tabulation, and chi-square tests to determine correlations between demographic factors and labour policy awareness. Qualitative insights were also gathered through open-ended interviews with HR personnel and union representatives[1].Findings indicate a significant lack of awareness among workers about key provisions of the labour codes, with notable variations across education levels and employment tenure. Many employees rely on informal sources of information, and there is limited institutional support for legal literacy. The study highlights the urgent need for targeted awareness programs, policy outreach, and stricter enforcement to ensure decent work conditions.This research contributes to the discourse on inclusive labour governance and emphasizes the importance of empowering SME workers with the knowledge required to safeguard their rights and improve compliance within the informal industrial ecosystem[2].